Hubungan Antara Pelaksanaan Program Hutan Kemasyarakatan dengan Kinerja Penyuluh Kehutanan di Provinsi Lampung - Yulistia Elena; Yuniar Aviati Syarief; Dewangga Nikmatullah (Fakultas Pertanian Universitas Jember, 2021)
Community forests are a tangible form of integration between forests as environmental buffers and providers of basic human needs, and the surrounding community as managers to benefit from forests. Community forest management is carried out by the community who must be given guidance by extension workers with a better role for community forest management. This study aims to determine the relationship between the implementation of the community forestry program and the performance of forestry extension workers. The research will be carried out at UPTD KPH Pematang Neba and UPTD KPH Batu Serob. Respondents for this research were forestry extension workers from the Lampung Provincial Forestry Service who were spread throughout the UPTD KPH, amounting to only 118 people. The research was conducted in August – October 2020. The method used in this study was a survey method. The relationship between the implementation of the HKm program and the performance of forestry instructors was analyzed using the Spearman rank test. The results showed that the relationship between the implementation of the HKm program and the performance of the forestry instructor was 0.556 with a significance value of 0.000, so it can be concluded that the implementation of the HKm program and the performance of the forestry instructor had a significant positive relationship. Keywords: Program Hutan Kemasyarakatan, Kinerja Penyuluh Kehutanan